Research in Geography Education in Light of ZGD 1973–2016 - Bagoly-Simó, Péter; Hemmer, Ingrid (Journal of Geography Education, 2017)
In recent years, German Geography Education has dedicated increasing attention to both its past development and future research perspectives. While similar approaches already existed as early as the 1970s, a systematic analysis of the development of research in the field was yet to be carried out. This paper explores coordinates of research development in Geography Education by analyzing the papers published in Geographie und ihre Didaktik (GuiD; as of 2014, Zeitschrift für Geographiedidaktik, ZGD), the flagship journal of the German Association of Geography Educators. The sample contained all papers published in the journal over the course of 45 years (i.e., 1973-2016). Content analysis served to explore formats, content, methods, and citations. The results show an overall increase of empirical papers at the expense of those focused on theory and teaching practice. Regarding content, the papers cover broad areas of Geography Education. In terms of research methods, quantitative approaches dominate. In recent years, the number of papers written in co-authorship increased. The analysis of citations shows an overall orientation towards research published in other subject educations and additional fields, such as Psychology of Education. Regarding gender, male and female authorship is represented in a balanced manner.
Keywords: research in Geography Education, meta-analysis, historic development, methods, content